2021
DOI: 10.3390/foods10020364
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Various Starchy Foods: A Systematic Review and Meta-Analysis on Chemical Properties Affecting the Glycemic Index Values Based on In Vitro and In Vivo Experiments

Abstract: The chemical properties that serve as major determinants for the glycemic index (GI) of starchy food and recommended low-GI, carbohydrate-based foods have remained enigmatic. This present work performed a systematic assessment of linkages between chemical properties of foods and GI, and selected low-GI starchy foods. The data were sourced from literature published in various scientific journals. In total, 57 relevant studies and 936 data points were integrated into a database. Both in vitro and in vivo studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 81 publications
(175 reference statements)
0
47
0
3
Order By: Relevance
“…Growing evidence indicates that naturally occurred phenolics have the potential to modulate carbohydrate digestion and glucose absorption through the inhibition of starch digestive enzymes and potential regulation of intestinal glucose transporters [58,59]. More recently, a systematic review and meta-analysis revealed that phenol levels in foods were negatively correlated with GI, and the mechanism was the inhibition of α-amylase and α-glucosidase [13]. Intake of 1 mg/mL of oat phenolics (either caffeic acid, chlorogenic acid, or ferulic acid) significantly suppressed (35-85%) glucose transport in rat intestinal brush boarder membrane vesicles [60].…”
Section: Phenolicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Growing evidence indicates that naturally occurred phenolics have the potential to modulate carbohydrate digestion and glucose absorption through the inhibition of starch digestive enzymes and potential regulation of intestinal glucose transporters [58,59]. More recently, a systematic review and meta-analysis revealed that phenol levels in foods were negatively correlated with GI, and the mechanism was the inhibition of α-amylase and α-glucosidase [13]. Intake of 1 mg/mL of oat phenolics (either caffeic acid, chlorogenic acid, or ferulic acid) significantly suppressed (35-85%) glucose transport in rat intestinal brush boarder membrane vesicles [60].…”
Section: Phenolicsmentioning
confidence: 99%
“…With regard to their effects on GI, current evidence mainly attributes them to oat phenolics. These bioactive components can reduce the absorption of glucose by inhibiting digestive enzymes, which is a potential therapeutic way to manage Type 2 diabetes [13]. However, more clinical trials are still needed to confirm the efficiency of this processing technique on oat GI.…”
Section: Bioprocesssingmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects were maintained after adjustment for BMI change suggesting that dietary change was the cause of their modulation. The amounts and composition of many foods and nutrients in the diet can influence glucose homeostasis, as reported for fruits, vegetables, fibre, protein, fats, and minerals [77]. However, there is now considerable evidence to suggest that dietary effects on glycemia are highly individualised, particularly during the postprandial phase after eating, challenging the notion of single glucose lowering diet [78].…”
Section: Serum Metabolites Modification By Exclusion Of Dairy and Limitation Of Fermented Foodsmentioning
confidence: 99%
“…Data dianalisis menggunakan nilai ukuran efek Hedges'd (Standardized Mean Difference/SMD) dengan nilai selang kepercayaan (Confidence interval/CI) 95% dan dikumpulkan dalam suatu model efek acak (random effects model) (Afandi, Wijaya, Faridah, Suyatma, & Jayanegara, 2021;Palupi, Jayanegara, Ploeger, & Kahl, 2012). Data-data yang sudah diinput ke dalam Microsoft Excel kemudian dihitung nilai S, J, d, Vd, Sd, Wd, Wd*d, D+, Vd+, Sd+ dan CI+ menggunakan lembar kerja yang pernah dikembangkan oleh Afandi (2020) berdasarkan rumus-rumus berikut :…”
Section: Analisis Statistikunclassified